Determination of Factors that Affect the Pregnancy Rate of Cows after Artificial Insemination at Monirampur Upazila of Jessore District of Bangladesh - D.M. Nazmul Hossain; Milton Talukder; Most. Kulsum Begum; Ashit Kumar Paul (The Korean Society of Animal Reproduction and Biotechnology, 2016)
This study was carried out to evaluate the influencing factors that affect the reproductive performance of cows at the Monirampur upazila in Jessore district of Bangladesh. A total of 224 cows were brought to the upazila livestock hospital for artificial insemination (AI). The cows were inseminated between 12 to 18 hours from the onset of estrus and data was obtained from the owner. Out of 224 cows, 133 became pregnant and 91 were non pregnant. In this study, the overall pregnancy rate was 59.29%. Among the age variability, the highest pregnancy rate (70.27%) was at the age of 4 years old. In case of breed variation, the highest pregnancy rate was observed in local breed (69.07%) compared with other crossbred cows. Hence the breed variations significantly influence the conception rate of cows. According to the parity, we found that the pregnancy rate was increasing with their parity but decreasing after 4th parity. The highest conception rate was observed in 3rd parity (67.74%) which was significantly higher than that of heifers (Parity-0). Here we also found that the types of bull semen used for AI had no significant effect for pregnancy rate. The skills of AI technician for AI to cows were significantly affecting the pregnancy rate. However, this study is not enough for rating and comment about the reproduction performance of cows. Therefore, further extensive study is needed for rating and recommendation for the cattle up gradation at that particular area.